KEPUTUSAN PEMBELIAN KONSUMEN DITINJAU DARI BRAND IMAGE, LIFE STYLE DAN MEDIA SOSIAL PADA VESPA METIC DI SURAKARTA - Enggar Arifina; Sudarwati Sudarwati; Ratna Damayanti (ITB AAS INDONESIA Surakarta, 2021)
The consumer's decision to buy a product starts from the awareness of fulfilling their needs, so in this study it is carried out because of the influence of the influence of brand image, lifestyle and social media on purchasing decisions at Vespa Metic in Surakarta, Vespa Metic users in Surakarta are the population in this study. Quantitative descriptive research, the sample obtained a number of 100 Vespa users, data obtained through questionnaires that have been distributed. Obtained from the analysis of the discussion, brand image, lifestyle and social media have a simultaneous and significant positive impact on purchasing decisions for Vespa Metic in Surakarta. Keywords: brand image, lifestyle and social media, purchasing decisions.